The Obstacles That Hamper the Success of Islamic Banking and Finance in Algeria - Elhachemi, Hacine Gharbi (2012)
The objective of this study is to show the concept, objectives, characteristics and the working mechanism of Islamic banking and financial system and to investigate the social, technical and legal obstacles that are confusing the Islamic banking in Algeria today. Questionnaires are designed and distributed to groups of senior staff in the nine public banks in the city of Boumerdes, Algeria. Multivariate statistical analysis is performed to analyze the data of this study. The results of the regression analysis indicate that all of the three hypotheses tested are supported. There is a positive effect and significant relationships between the technical and social obstacles and the adoption of Islamic Banking in Algeria. Where the legal obstacle has a negative correlation within the adoption of Islamic Banking in Algeria. These variables are significantly and highly correlated with the adoption of Islamic Banking initiatives.These results proved that there are many social, legal and technical obstacles which hamper the success of Islamic banking and finance in Algeria.